З історії розвитку договору найму (оренди) земельних ділянок - Самчук-Колодяжна, З.; Samchuk-Kolodiazhna, Z. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено історію розвитку цивільно-правових договорів найму (оренди) земельних ділянок з огляду на те, що ці відносини врегульовуються низкою спеціальних законів із перевагою вимог земельного та господарського законодавства. Саме цивільно-правові договори покликані забезпечити раціональне вико- ристання земель і повноцінний та легальний обіг земельних ділянок.The article deals with the history of civil contracts such as the land hire (rent) agreements. Such relations are governed by a number of special laws to meet the requirements of land and economic legislation.The civil contracts are designed to ensure the rational use of land, as well as a full and legal circulation of land. The use of farm-lands is of great importance nowadays. It should be noted that lease relations are established in accordance with such lands, and the law throughout the history of its development is trying to regulate such lease relations properly due to the fact of the absence of land market in the USSR and at the present time. Today condemnation of the farm-land is in moratorium. The key issues and features of land rent regulations by national law are examined in the article. Conclusion of contracts for the rights to use the land for agricultural purposes or for building in accordance with the Civil Code of Ukraine with the requirements of the Land Code of Ukraine.
From the History of the Land hire (rent) Agreement
Keywords: оренда; найм; цільове використання; земельна ділянка; володіння та користування; rent; lease; permitted use; land; possession and enjoyment